IMPLEMENTASI KONSEP TRI HITA KARANA DALAM PERSPEKTIF KEHIDUPAN GLOBAL: BERPIKIR GLOBAL BERPERILAKU LOKAL - I Putu Gede Parmajaya (Purwadita : Jurnal Agama dan Budaya, 2018)
The decline of morality, honesty and spiritual values of some Indonesian people in theform of dependence on illicit drugs such as drugs, child sexual abuse, infidelity spread amongthe community. The values of honesty, exemplaryity, fragility of character, identity, crisis ofconfidence and moral degradation are not only among teenagers, but also in old people whoshould provide guidance and guidance to the young generation, corruption among officialsgovernment with the number of occurring (hand-catch operation) as a sign that humans at thistime have no shame. Because only humans can and can practice the teachings of tri hita karanain everyday life. Human beings who have talent in terms of idep (mind) should strive to implementthe teachings of tri hita karana in everyday life with always God Almighty. Humans must endeavorto preserve the natural environment by replanting, maintaining the environment and maintaininganimals in accordance with the procedures and striving to always care about the environmentthat has been increasingly damaged. Take advantage to good karma in the opportunity to live inthe birth of a human being equipped with advantages, especially the potential of EyelashKeywords: Tri Hita Karana, Global Life, Local Behavior